Evaluating the efficacy of different botanicals on prolonging shelf life and maintaining quality of mandarin (Citrus reticulate Blanco var. Banshkharka Local) - Khanal, Asmita; Timilsina, Sandip; Poudel, Neela; Khanal, Susmita; Poon, Tul Bahadur (Archives of Agriculture and Environmental Science, 2023)
Mandarin (Citrus reticulate Blanco) has been cultivated in 56 districts of Nepal. Huge losses in mandarin were reported and use of safer alternatives to synthetic chemicals to solve post-harvest losses is a matter of great concern. An experiment was conducted at the Directorate of Agricultural Research, Lumle for two consecutive years 2019 and 2020. Mandarin having similar maturity indices were harvested and transported to DoAR, Lumle. The fruits were treated with five different botanicals (garlic extract @ 10 %, ginger extract @ 10 %, aloe vera extract @ 10 %, neem extract @ 10 %, and control) allocated in randomized complete block design with four replications. The post-harvest study was conducted for 3 weeks under laboratory conditions (7.9 ± 3° C and RH 74 ± 4%). Different parameters such as physiological loss in weight (PLW), decay loss, total soluble solid (TSS), titrable acidity (TA) and fruit weight to juice ratio were recorded. Fruit treated with ginger extract @ 10 % recorded the minimum physiological loss in weight (6.31% and 5.15%), minimum decay loss (16 % and 17%) in the year 2019 and 2020, respectively. Highest TSS: TA ratio (13.54 and 12.79) and fruit weight to juice ratio (0.33 and 0.35) was also observed in fruit treated with ginger extract @ 10 % in both years. In both years, results obtained in the fruits treated with ginger extract was followed by fruit treated with aloe vera extract and garlic extract. Control treatment gave the poor result as compared to ginger extract @ 10 %. Thus, this study concluded that the use of ginger is suitable for postharvest treatment of mandarin fruit to increase its shelf life and maintain its quality parameters.